High parathyroid hormone levels after parathyroidectomy for parathyroid adenoma are not related to the cellularity of the remaining glands. Issue 5 (8th September 2021) - Sagiv, Rotem; Delgado, Bertha; Sadeh, Re'em; Shashar, Sagi; Fraenkel, Merav; Yegodayev, Ksenia M.; Elkabets, Moshe; Joshua, Ben‐Zion
Abstract: Background: Patients with primary hyperparathyroidism (PHPT) treated surgically occasionally have normalized calcium, but persistently high parathyroid hormone (PTH). We hypothesized that a possible explanation for this phenomenon is an underlying hyperplasia rather than adenoma. Methods: Retrospective cohort of patients who underwent parathyroidectomy for PHPT with biopsy of a normal‐appearing parathyroid gland were included. Cellularity level of each biopsy and of the adenoma's rim was determined. Results: Forty‐seven patients were included. Of them, 19 (40%) had postoperative normocalcemia but elevated PTH. There was no correlation between cellularity either in the rim or of the normal‐appearing parathyroid gland and postoperative PTH. The postoperative high PTH group had higher preoperative PTH ( P  = 0.001) and larger adenomas ( P  = 0.025). Conclusions: High PTH levels after successful parathyroidectomy in patients with primary hyperparathyroidism do not appear to result from underlying hyperplasia. A possible alternative explanation is that these patients have a higher preoperative burden of disease. Abstract : Patients with Primary hyperparathyroidism treated surgically occasionally have normalized calcium, but persistently high PTH. We hypothesized that a possible explanation for this phenomenon is an underlying hyperplasia rather than adenoma.? Contrary to our hypothesis, there was no correlation between the cellularity of the normal‐appearing parathyroid glands and the parathyroid tissue surrounding the adenoma with PTH levels after surgery.